EFEKTIVITAS JUS APUKAT TERHADAP PENURUNAN NYERI HAID (DISMENOREA) PADA REMAJA PUTRI - Nurmaliza Nurmaliza; Rini Hariani Ratih; Yusmaharani Yusmaharani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
In Indonesia, the incidence of dysmenorrhea is 64.25%. Based on the data shows that primary dysmenorrhoea is experienced by 60-75% of young women. About 25% of women experience it and it is found mostly in women aged 20 years. Avocado contains vitamin B6, vitamin E, calcium and magnesium to reduce PMS symptoms. The purpose of this study was to determine the effectiveness of avocado juice against reducing menstrual pain in young women at SMAN 7 Pekanbaru. This type of research is quantitative with a Quasi-Experimental research design. This research was conducted from October 2021 to June 2022. The population of this study was 23 young women in class XI of SMAN 7 Pekanbaru in 2022 who experienced mild and moderate pain. The total sample of 15 people with stratified random sampling with a pre-test & post-test design Data analysis used is univariate and bivariate. The results of the study, based on the Wilcoxon test obtained a P-value of 0.001 > α 0.05 then Ha was accepted meaning that there is an effectiveness of avocado juice against reducing menstrual pain ( Dysmenorrhoea) Adolescents at SMAN 7 Pekanbaru in 2022. It is hoped that the research site will be able to provide information on the Effectiveness of avocado juice against reducing menstrual pain as a non-pharmacological drug in young women.